2018
DOI: 10.1002/mds.27296
|View full text |Cite
|
Sign up to set email alerts
|

New Developments in Genetic rat models of Parkinson's Disease

Abstract: Preclinical research on Parkinson's disease has relied heavily on mouse and rat animal models. Initially, PD animal models were generated primarily by chemical neurotoxins that induce acute loss of dopaminergic neurons in the substantia nigra. On the discovery of genetic mutations causally linked to PD, mice were used more than rats to generate laboratory animals bearing PD-linked mutations because mutagenesis was more difficult in rats. Recent advances in technology for mammalian genome engineering and optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 139 publications
(303 reference statements)
0
36
0
1
Order By: Relevance
“…disease as complex as PD, it would still be interesting to verify whether FTY720 and SEW2871 provide also protection during the formation of a-synuclein aggregates that resemble Lewy bodies or Lewy neurites. For instance, chronic administration of neurotoxins induces progressive PD rodent models that include a-synuclein aggregates in addition to motor deficits and rapid nigrostriatal dopaminergic cell death (Creed and Golberg, 2018). Furthermore, genetic-based approaches including transgenic models, viral vector-mediated models based on genes linked to monogenic PD as well as introduction of a-synuclein preformed fibrils all induce toxic protein aggregates in rodents.…”
Section: Pépin Et Almentioning
confidence: 99%
“…disease as complex as PD, it would still be interesting to verify whether FTY720 and SEW2871 provide also protection during the formation of a-synuclein aggregates that resemble Lewy bodies or Lewy neurites. For instance, chronic administration of neurotoxins induces progressive PD rodent models that include a-synuclein aggregates in addition to motor deficits and rapid nigrostriatal dopaminergic cell death (Creed and Golberg, 2018). Furthermore, genetic-based approaches including transgenic models, viral vector-mediated models based on genes linked to monogenic PD as well as introduction of a-synuclein preformed fibrils all induce toxic protein aggregates in rodents.…”
Section: Pépin Et Almentioning
confidence: 99%
“…Subsequent studies of the same line of PINK1-/- rats reported mitochondrial dysfunction, behavioral deficits, loss of neurons in the substantia nigra and locus coeruleus, neurochemical abnormalities and α-synuclein aggregates in various brain regions (Grant et al, 2015; Kelm-Nelson et al, 2015, 2016, 2018; Pultorak et al, 2016; Stauch et al, 2016a,b; Villeneuve et al, 2016a,b). We sought to further characterize PINK1-/- rats specifically with respect to α-synuclein pathology because spontaneous formation of α-synuclein aggregates (without α-synuclein overexpression or injection) is a rare and important feature of PD animal models and because α-synuclein aggregation has been implicated both genetically and biochemically as a mechanism of PD pathogenesis as well as a potential therapeutic target (Goldberg and Lansbury, 2000; Creed and Goldberg, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…PINK1 is a gene involved on early-onset PD. Pink1-KO rats have mitochondrial abnormalities, and proteinase K-resistant aSyn aggregates in different brain regions [40,41] . Additionally, rats exhibit significant vocalization deficits dependent on age, intensity, bandwidth, and peak frequency [39] .…”
Section: Hypokinetic Dysarthriamentioning
confidence: 99%